KEADILAN DISTRIBUTIF, KEADILAN PROSEDURAL, DAN KOMITMEN TUJUAN ANGGARAN SEBAGAI PEMEDIASI PARTISIPASI PENGANGGARAN PADA KINERJA MANAJERIAL - Wiguna Giri, Dwi Baskara (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.03.NO.04.TAHUN 2014, 2014)
Managerial performance based on how much the manager is able to carry out management functions including planning, investigation, coordination, evaluation, supervision, staff selection, negotiation, and representation. Managerial performance is said to be effective if the goal can be achieved budget and get a chance subordinates engage or participate in budgeting. Previous research on the effect of budgetary participation on managerial performance finding inconsistent results. The purpose of this study was to determine the effect of budgetary participation on managerial performance with distributive justice, procedural fairness, and commitment budgetary purposes as mediating variables. The study was conducted in 2013. The data was collected using a questionnaire, with 37 mid-level managers Sanglah as respondents. Respondents were selected by purposive sampling method. The analysis technique used was Partial Least Square (PLS). The research instrument has passed the test of validity and reliability. Statistical analysis showed that the effect on the budgetary participation and managerial performance with distributive justice, procedural fairness, and commitment budgetary purposes as mediating variables.